Infrared emitting material using infrared wavelength manipulation. (December 2020) - Lim, Taekyung; Lee, Tae Kyung; Jeong, Sang-Mi; Pak, Jeong Hyeok; Choi, Yong Kyu; Kwak, Sang Kyu; Ju, Sanghyun
Highlights: An infrared display device allows the selective visualization or concealment of information. Infrared-emitting pixel array is integrated on the transparent substrate. Full-color infrared image is generated by controlling different IR intensities. Infrared emitting characters, figures, and videos were displayed. Dual display combined with infrared display and visible light display is possible. Abstract: Infrared (IR) display technology implements a display using IR radiation. Whereas ordinary visible displays that output digital data in the visible spectral range are detectable to human eyes, an IR display outputs data outside the visible spectral range. This study looks at the possibility of expanding the color-replication spectrum beyond the visible range by applying IR wavelength separation techniques. We developed a new display technology that uses the same driving method as general display technology but emits IR radiation that cannot be seen by humans. The IR wavelength region was separated into three regions, similar to the RGB regions of visible displays, and an IR display capable of outputting images and movies was produced by combining these IR emissions. The implementation of various characters, figures, and videos was demonstrated. The present method can be applied to the production of single displays based on IR radiation, as well as to the production of multi-displays whereby an IR display is mounted on top of a visible light display on a single device. This technology can be used to provide a smart digital information environment where humans can selectively visualize or conceal information. Graphical abstract: An infrared display device is created that can actively show or hide information from humans by extending the wavelength used in the display from visible to infrared light. Image, graphical abstract